1993
DOI: 10.1063/1.354628
|View full text |Cite
|
Sign up to set email alerts
|

Exciton luminescence in Si1−xGex/Si heterostructures grown by molecular beam epitaxy

Abstract: Coherent Si1−xGex alloys and multilayers synthesized by molecular beam epitaxy (MBE) on Si(100) substrates have been characterized by low-temperature photoluminescence (PL) spectroscopy and transmission electron microscopy (TEM). Phonon-resolved transitions originating from excitons bound to shallow impurities were observed in addition to a broad band of intense luminescence. The broad PL band was predominant when the alloy layer thickness was greater than 40–100 Å, depending on x and the strain energy density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 40 publications
3
24
1
Order By: Relevance
“…Initially, Ge atoms form small 2D platelets that evolve into pre-pyramids 22 as the Ge coverage is increased. Further deposition leads to the formation of well-defined square pyramids or elongated pyramids, or so called hut-clusters, 2 with side-walls oriented along [105] crystallographic directions [Figs. 2(a) and 2(b)].…”
Section: A Growth and Shape Evolutionmentioning
confidence: 99%
“…Initially, Ge atoms form small 2D platelets that evolve into pre-pyramids 22 as the Ge coverage is increased. Further deposition leads to the formation of well-defined square pyramids or elongated pyramids, or so called hut-clusters, 2 with side-walls oriented along [105] crystallographic directions [Figs. 2(a) and 2(b)].…”
Section: A Growth and Shape Evolutionmentioning
confidence: 99%
“…Photoluminescence (PL) provides accurate measurement of the SiGe band gap in unstrained (cubic) alloys [1] and strained SiGe [2] epitaxially deposited on (001) Si. Quantum confinement effects [3] and SiGe/Si interface integrity [4] have also been studied by PL. However, evidence of the band lineup at the SiGe/Si heterointerface has remained elusive.…”
mentioning
confidence: 99%
“…The alloy layer luminescence energy exhibits the same dependence on x as the bulk energy gap, but it is at an overall lower energy Rowell et al, 1990;Sturm et al, 1991;Lenchyshyn et al, 1992). The recombination mechanism can vary depending on the alloy layer thickness, its crystalline quality, and the heterointerface sharpness and can give rise to near band-edge light emission and/or excitonic luminescence (Noël et al, 1992;Lenchyshyn et al, 1993;Rowell et al, 1993). In early work, it was found that the EL from Si1−xGex/Si p-i-n diodes was quenched when the temperature was increased above 80 K , but EL was later reported at higher temperatures (up to 220 K) in p-i-n diode structures (Robbins et al, 1991).…”
Section: Band Structure Engineering Via Alloyingmentioning
confidence: 98%